Rede de Bragg aplicada na monitoração da deformação mecânica de verniz acrílico durante a secagem - Oliveira, Fernanda Mantuan Dala Rosa de (2013)
This work shows the application of an optical sensor based on fiber Bragg grating (FBG) to monitor the drying process of polymers. Tests carried out with acrylic varnish showed that a fiber Bragg grating can be used as a sensor to analyze the deformation of a polymeric film during the drying process without any special encapsulation of the sensor. The drying process of a varnish film was monitored over 24 hours by two Bragg gratings, one of them acting as a mechanical deformation sensor and the other one as temperature sensor. Measurements of mass loss were also performed. The results allow evaluating mechanical deformations and identifying three stages of drying: evaporation of water and concentration of solids, irreversible particle contact and coalescence process, and finally, formation of a continuous film.